2011
DOI: 10.1093/aob/mcr300
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies of thermotolerance: different modes of heat acclimation between tolerant and intolerant aquatic plants of the genus Potamogeton

Abstract: Our comparative study of thermotolerance showed that heat acclimation leads to species-specific changes in heat response. The development of acquired thermotolerance is beneficial for survival at extreme temperatures. However, the loss of acquired thermotolerance and plasticity in the minimum threshold temperature of heat response may be favourable for plants growing in moderate habitats with limited daily and seasonal temperature fluctuations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 59 publications
1
35
0
2
Order By: Relevance
“…Increasing evidence shows that alternative splicing (AS) is a critical posttranscriptional event and plays an important role in plant stress responses (Mazzucotelli et al, 2008;Mastrangelo et al, 2012). However, the AS of Hsfs in plants is largely unknown, although AS events have been experimentally identified in a few plant genes, including alfalfa (Medicago sativa) Hsf1 (He et al, 2007), Arabidopsis HsfA2 (Sugio et al, 2009), and genus Potamogeton HsfA2a2 (Amano et al, 2012). These Hsf splice variants contain premature termination codons and are degraded through the nonsense-mediated mRNA decay (NMD; He et al, 2007;Sugio et al, 2009;Amano et al, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence shows that alternative splicing (AS) is a critical posttranscriptional event and plays an important role in plant stress responses (Mazzucotelli et al, 2008;Mastrangelo et al, 2012). However, the AS of Hsfs in plants is largely unknown, although AS events have been experimentally identified in a few plant genes, including alfalfa (Medicago sativa) Hsf1 (He et al, 2007), Arabidopsis HsfA2 (Sugio et al, 2009), and genus Potamogeton HsfA2a2 (Amano et al, 2012). These Hsf splice variants contain premature termination codons and are degraded through the nonsense-mediated mRNA decay (NMD; He et al, 2007;Sugio et al, 2009;Amano et al, 2012).…”
mentioning
confidence: 99%
“…However, the AS of Hsfs in plants is largely unknown, although AS events have been experimentally identified in a few plant genes, including alfalfa (Medicago sativa) Hsf1 (He et al, 2007), Arabidopsis HsfA2 (Sugio et al, 2009), and genus Potamogeton HsfA2a2 (Amano et al, 2012). These Hsf splice variants contain premature termination codons and are degraded through the nonsense-mediated mRNA decay (NMD; He et al, 2007;Sugio et al, 2009;Amano et al, 2012). Thus, AS-NMD may be involved in regulating the level of full-length mRNAs of these three plant Hsfs.…”
mentioning
confidence: 99%
“…Previous studies on animals (Sorensen and Loeschcke 2001;Buckley et al 2001;Tomanek 2010) and plants (Knight and Ackerly 2003;Barua et al 2008;Knight 2010;Amano et al 2012) have shown variability in the threshold temperature needed to induce the HS response, and differences exist among species in the levels of HSPs expressed during stress. In a study of the plant Encelia (E. formosa from the Mojave desert and E. californica from the coast), it was reported that the desert species, E. formosa, produced more sHSPs above 45°C than the coastal species (E. californica) did.…”
Section: Relationship Of Thermotolerance Patterns To Species Habitatmentioning
confidence: 97%
“…Studies of the chloroplast sHSPs (Knight andAckerly 2001, 2003;Barua et al 2003;Wang and Luthe 2003;Knight 2010) have found varying levels of HSP gene expression and differences in organismal thermotolerance. More recently Amano et al (2012) reported differences in HSF and HSP (specifically CP-sHSP) gene expression and significant differences in thermotolerance in two Potamogeton species. Other studies in plants have shown the some HSP genes have undergone positive selection (Wu et al 2007) and that differences in expression levels can have fitness consequences (Tonsor et al 2008).…”
Section: Introductionmentioning
confidence: 98%
“…Warming may decrease photosynthesis and increase respiration (Ryan 1991), thereby impacting the distribution, modes of reproduction, germination, growth, and dormancy of freshwater SAV (Welch 1952;Barko and Smart 1981;Lacoul and Freedman 2006). However, the response of freshwater aquatic plants to climate warming is species-specific, and varies even for locally adapted "biotypes" (e.g., Barko and Smart 1981;Pip 1989;Svensson and Wigren-Svensson 1992;Santamaría and Van Vierssen 1997;Rooney and Kalff 2000;Sala et al 2000;Amano, Iida, and Kosuge 2012). Some species exhibit earlier germination and increased productivity, while others do not (Mckee et al 2002;Lacoul and Freedman 2006).…”
Section: A Warming Estuarymentioning
confidence: 99%